The Concept of Liberation in the Qur'an as Practiced in the History of Islamic Education - Yulianto, Nunung; Wantini, Wantini (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2022)
This study intends to elucidate on the concept of liberation in the Qur'an through the Prophet Muhammad's educational process. This study employs a library research methodology. The analysis results indicate that the first verse of the Koran revealed was an instruction to read. He was pivotal to the development of science. The Prophet Muhammad was sent to a society that was replete with ignorance. By means of the Qur'an, the Prophet transformed and emancipated primordial humans into a sophisticated civilization. The Prophet Muhammad transformed and emancipated all aspects of human existence, including faith, worship, education, social and community culture. Muhammad's accomplishment was inextricable from a number of challenges and obstacles. The spirit of change and liberation was then transmitted from generation to generation to family and friends until the golden period of Islam in the Middle Ages. During this time, Muslim scientists who successfully acquired knowledge by studying the Koran were born.